Management and clinical outcomes of follicular lymphoma across continuous lines of treatments: a retrospective analysis in China - Liu, Jiaxin; Hu, Yunfei; Zhao, Linjun; Nuersulitan, Reyizha; Liu, Yanfei; Yu, Hui; Ye, Yingying; Wang, Dedao; Tang, Yongjing; Feng, Feier; Liu, Weiping; Zhu, Jun; et al. (Frontiers in Oncology, 2023)
Background: Follicular lymphoma (FL) is characterized by an incurable course that frequently necessitate multiple lines of treatment. While a range of new approaches have broadened therapeutic options for patients in later lines, data regarding treatment patterns and outcomes of Chinese patients with relapsed/refractory(R/R) FL was scarcely reported. Methods: This retrospective single-center study included patients diagnosed with FL grade 1–3a at our institution between January 2002 and December 2019. Endpoints of interest were analyzed according to lines and types of interventions. The endpoints mainly included overall response rate (ORR), progression-free survival (PFS), and overall survival (OS). Results: The study enrolled 566 biopsy-proven patients. Among them, 544 patients initiated 1st-line of treatment, followed by 240 initiating 2nd-line, 146 initiating 3rd-line, 88 initiating 4th-line, 47 initiating 5th-line and 28 initiating 6th-line. In terms of treatment patterns, anti-CD20 chemotherapy was major modality in the 1st- and 2nd-line. However, for patients in the 3rd-line and subsequent lines, treatment approaches were diverse, and participation in clinical trials for new medications was common, which correlated with a survival benefit. The study also revealed that clinical indicators (such ORR, PFS and OS) gradually decreased with each subsequent line of treatment. The ORR at the 1st-line was 86.6%, but decreased to 48.6% at the 3th-line and 40.4% at the 6th-line, respectively. Similarly, median OS and PFS decreased to 88.8 and 7.1 months at the 3rd-line, and further reduced to 21.7 and 2.8 months at the 6th-line, respectively. A total of 133 patients developed progression within 24 months from initiation of 1st-line anti-CD20 chemotherapy (POD24) and these patients exhibited poorer response rates and outcomes in subsequent lines of therapies compared to the non-POD24 group. Conclusion: This study revealed the clinical routine practices and prognosis of R/R FL patients within Chinese population. It underscored the unmet need for optimal strategies to improve survival and also served as a benchmark for future trials.